1970
DOI: 10.19184/ams.v1i2.1954
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Inhibit the Effect of Pioglitazone in Reducing MMP-9 and MMP-13 of IL-1β-Induced Chondrocytes

Abstract: AbstrakOsteoarthritis (OA) merupakan penyebab nyeri sendi tersering, namun hingga kini masih belum ada terapi yang memuaskan yang mampu menghambat kerusakan pada kartilago sendi OA. Salah satu pendekatan yang sedang banyak diteliti adalah melalui aktivasi PPAR-γ. Dan telah banyak penelitian pula yang sudah membuktikan tentang efek PPAR-γ pada OA baik in vitro maupun in vivo pada hewan coba. Di sisi lain, faktor resiko utama dari OA adalah obesitas. Pada obesitas umumnya diikuti meningkatnya kadar leptin akibat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…MMP-9 is a gelatinase, and activated MMP-9 can directly degrade ECM and promote the occurrence and development of physiological and pathological osteolysis. It was widely believed that MMPs are involved in the occurrence and development of cartilage degenerative changes, and MMP-13 and MMP-9 play an important role in the degradation of cartilage extracellular matrix [19]. In this study, we found that the expression levels of SDF-1, CXCR4, MMP-9, and MMP-13 in KOA rats increased, which is consistent with reports in the literature.…”
Section: Discussionsupporting
confidence: 92%
“…MMP-9 is a gelatinase, and activated MMP-9 can directly degrade ECM and promote the occurrence and development of physiological and pathological osteolysis. It was widely believed that MMPs are involved in the occurrence and development of cartilage degenerative changes, and MMP-13 and MMP-9 play an important role in the degradation of cartilage extracellular matrix [19]. In this study, we found that the expression levels of SDF-1, CXCR4, MMP-9, and MMP-13 in KOA rats increased, which is consistent with reports in the literature.…”
Section: Discussionsupporting
confidence: 92%